2020
DOI: 10.1177/0193723520919816
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study Exploring the Experiences of a Transgender Athlete in Synchronized Skating, a Subdiscipline of Figure Skating

Abstract: The inclusion of transgender athletes in sport challenges a number of long-standing cis-heteronormative beliefs within athletics at all levels of competition. There are limited studies examining the integration and experiences of transgender athletes within amateur sport. The following case study follows the experiences of a transgender synchronized figure skater, Mason, who was able to continue competing throughout his transition process. We conducted eight semi-structured one-on-one interviews with Mason, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Athletes have muscular aerobic endurance. 10 An athlete's body composition also has many degrees of influence on its specific movement speed and specific explosive power. An athlete's performance in competition may also reflect body composition characteristics.…”
Section: Authors' Contributionsmentioning
confidence: 99%
“…Athletes have muscular aerobic endurance. 10 An athlete's body composition also has many degrees of influence on its specific movement speed and specific explosive power. An athlete's performance in competition may also reflect body composition characteristics.…”
Section: Authors' Contributionsmentioning
confidence: 99%
“…social networks, mailing lists, and websites) as well as tailored advertisements in online platforms and snowball techniques López-Cañada et al, 2020;. Snowball techniques are also applied in qualitative studies, often combined with personal contacts in advance (Herrick et al, 2020;Travers & Deri, 2011) or help from specific institutions (e.g. health services; .…”
Section: Recruitment and Samplingmentioning
confidence: 99%
“…Many qualitative researchers reflect on their specific gender (identity), sexual orientation, race, body-related abilities, etc., with regard to their premises and lenses of interpretation when collecting data, approaching respondents, etc. Elling & Collot d'Escury, 2017;Herrick et al, 2020). Regarding researcher positioning, Herrick et al (2020, p. 6) pointed out that their "research has been guided through the lens of the first author's experiences as a self-identified able-bodied white queer cis-femme settler", while the other authors similarly provided their own positionings.…”
Section: Researcher Reflexivitymentioning
confidence: 99%
“…Educational institutions-among others-appear to have listened to these concerns, as gender-neutral options are becoming increasingly common (Laidlaw, 2020;Barkowsky et al, 2019;Brock University, 2019). However, many TGNC people still continue to use gendered spaces and/or continue their avoidance of all public facilities due to a variety of factors, such as ineffective communication of gender-neutral options by institutions (Laidlaw, 2020), a social desire to remain with their peer group (Beese & Martin, 2018), and/ or a sense of affirmation from accessing gendered spaces congruent with their gender identity (Herrick et al, 2020;Oakleaf & Richmond, 2017).…”
Section: Introduction: the Rise Of Gender-neutral Facilities And Thei...mentioning
confidence: 99%
“…However, we observe that this solution may have drawbacks, in sites including but not limited to university campuses. Single-user facilities can also increase social isolation and reduce opportunities for interpersonal connection (Herrick et al, 2020). Multi-user facilities can be important spaces to socialize with peers (Cunningham et al, 2017;Herrick et al, 2020;Kjaran, 2019).…”
Section: Introduction: the Rise Of Gender-neutral Facilities And Thei...mentioning
confidence: 99%